Comprehensive Metabolomics and Network Pharmacology to Explore the Mechanism of 5-Hydroxymethyl Furfural in the Treatment of Blood Deficiency Syndrome - Zhang, Wensen; Cui, Na; Su, Fazhi; Wang, Yangyang; Yang, Bingyou; Sun, Yanping; Guan, Wei; Kuang, Haixue; Wang, Qiuhong (Frontiers in Pharmacology, 2022)
Radix Rehmanniae (RR, from Radix Rehmanniae (Gaertn.) DC.) is a natural medicine used in traditional Chinese medicine (TCM) since ancient times for the treatment of blood disorders. RR is steamed to get Rehmanniae Radix Praeparata (RP), which has a tonic effect on blood; the content of 5-hydromethylfurfural (5-HMF) increases more than four times after steaming. Studies have shown that 5-HMF has positive pharmacological effects on cardiovascular and hematological disorders. This study aimed to explore and verify the impact of 5-HMF on rats with chemotherapy-induced blood deficiency syndrome (BDS). Rats were given cyclophosphamide (CP) and acetophenhydrazine (APH) to induce BDS, the coefficients of some organs (liver, spleen, and kidney) were measured, and a routine blood test examined the coefficients of several peripheral blood cells. Metabolomics and network pharmacology were combined to find important biomarkers, targets, and pathways. And Western blot was used to detect the expression of CYP17A1 and HSD3B1 proteins in the spleen. All these findings suggested that the 5-HMF significantly increased the number of peripheral blood cells and reversed splenomegaly in rats. In addition, 5-HMF upregulated CYP17A1 and HSD3B1 protein expression in splenic tissues. Also, 5-HMF ameliorated chemotherapy-induced BDS in rats, and its therapeutic mechanism might depend on steroid hormone biosynthesis and other pathways. It acts on blood deficiency via multiple targets and pathways, which is unique to Chinese medicine.